Cam ring curve optimization for radial hydraulic motor based on seagull algorithm - Zhang, Bowen (Strojniški vestnik, 2025)
With the accelerated adjustment of the global energy structure, the intensity of strategic mineral resource development continues to rise. The growing demand for construction machinery and equipment has led to increased use of radial piston hydraulic motors, known for their low-speed and high- torque characteristics, in heavy-duty mining machinery and equipment. However, the cam ring curve design of a radial piston hydraulic motor still faces critical challenges, including significant contact stress, and noticeable output pulsation. To address these issues, this paper proposes a multi-step composite curve optimization design method based on the seagull optimization algorithm (SOA). This method integrates the concepts of stepped and trapezoidal acceleration curve design, utilizing the SOA algorithm to tackle these challenges. The SOA algorithm is more adaptive than the genetic algorithm and the particle swarm optimization algorithm, maintaining population diversity even in the later stages of iteration. This effectively overcomes the limitations of the particle swarm optimization and genetic algorithm in multi-peak problems. A cam ring curve optimization model is established to minimizing contact stress through theoretical modeling and dynamics analysis. Using the combined global search and local exploitation capabilities of SOA, we achieved multi-constraint optimization on key parameters such as the amplitude-angle ratio in the acceleration zone and the amplitude-angle in the zero-speed zone. This results in a composite cam ring curve characterized by reduced stress, low pulsation, and shock-free operation. The effectiveness of this method was validated through bench tests, which showed that the maximum contact stress of the optimized multistep composite curve at a speed of 100 rpm is reduced by 5.4 % and 18.3 % compared to the conventional equal acceleration curve and trapezoidal curve, respectively. Additionally, the speed pulsation rate decreases by 10.81 % and 25.73 % under 20 MPa and 30 MPa conditions, respectively, with no sudden change in reaction force and a reduction in pulsation shock during operation.
Keywords: algoritem optimizacije obnašanja galebov; cam ring optimization; contact stress; kontaktna napetost; optimizacija odmikalnega obroča; pulzacija hitrosti; radial piston hydraulic motor; radialni batni hidravlični motor; seagull optimization algorithm; speed pulsation